Respuesta :
The result of subtracting the second equation from the first is [tex]y = \frac{3}{4}[/tex]
Solution:
Given system of equations are:
-3x + 2y = 7 ----- eqn 1
and -3x - 2y = 4 ---- eqn 2
We have to find the result of subtracting the second equation from the first
So we have to subtract second equation from the first
-3x - 2y = 4
-3x + 2y = 7
(-) -----------------
-4y = -3
4y = 3
[tex]y = \frac{3}{4}[/tex]
Thus the result of subtracting the second equation from the first is [tex]y = \frac{3}{4}[/tex]